SELF ESTEEM TERHADAP SUBJECTIVE WELL BEING PADA BURUH SOPIR PENGANGKUT PETI KEMAS - Windy Febi Aulia (Jurnal Ilmiah Psyche, 2020)
This study aims to determine whether or not there is a relationship between self esteem and subjective well being on driver workers in container transportation PT. Tri Trans Wijaya Palembang. The population of this study is all container driver PT. Tri Trans Wijaya Palembang totaling 46 people. The data collection tool used in this study is the scale of self esteem and the scale of subjective well being. This analysis using correlation techniques from Pearson's product moment. The researcher didn’t use sample techniques but used populat ion techniques because the population was 46 container drivers PT. Tri Trans Wijaya which all the drivers become the subject of this study. The results from this study showed that there was a positive relationship between Subjective Well Being and self esteem in container drivers PT. Tri Trans Wijaya Palembang. This relationship is indicated by the r-count correlation coefficient of 0,375 and r-table of 0.291. Thus r-count> r-table. This result informs that the more precisely self esteem, the higher the subjective well being will be, and vice versa. The conclusion in this study showed there is a relationship between self esteem and subjective well being on on driver workers in container transportation PT. Tri Trans Wijaya.